Walzer and War
XVI, 275 p. 1 illus.
Keywords: This book presents ten original essays that reassess the meaning, relevance, and legacy of Michael Walzer’s classic, Just and Unjust Wars. Written by leading figures in philosophy, theology, international politics and the military, the essays examine topics such as territorial rights, lessons from America’s wars in Iraq and Afghanistan, the practice of humanitarian intervention in light of experience, Walzer’s notorious discussion of supreme emergencies, revisionist criticisms of noncombatant immunity, gender and the rights of combatants, the peacebuilding critique of just war theory, and the responsibility of soldiers for unjust wars. Collectively, these essays advance the debate in this important field and demonstrate the continued relevance of Walzer’s work. Graham Parsons is Associate Professor in the Department of English and Philosophy at the United States Military Academy at West Point, USA and was previously Fellow at the Individualisation of War Project, European University Institute, Italy. Mark A. Wilson is a Teaching Professor of Ethics and was previously Chair of the Returning Soldiers Project at Villanova University, USA.